Women and Extremism: A Feminist Analysis of European Female ISIS Recruits - Sarah Hajar Mahmudah (Mimbar Agama dan Budaya, 2023)
This study investigates the active participation of European women, particularly British citizens, in ISIS's operations and propaganda, which challenges traditional gender norms and perceptions of Muslim women in Western societies. The research used postmodern feminist theory to delve into the multifaceted motivations driving these women—from feelings of alienation and promises of empowerment to ideological aspirations—and examines their roles as recruiters, propagandists, and enforcers within the al-Khansaa Brigade. Specific cases, such as Aqsa Mahmood, illustrate the strategic use of social media to romanticize life in the caliphate while simultaneously exploiting women through constructs like "sexual jihad." The phenomenon reflects a paradox where agency is wielded within deeply patriarchal structures, perpetuating both empowerment and subjugation. Additionally, the paper explores the societal factors fueling radicalization, including Islamophobia and systemic discrimination, and highlights the challenges of reintegration for women returning to their home countries. By addressing the gendered dynamics of terrorism, this study underscores the importance of inclusive counterterrorism strategies that dismantle extremist narratives and foster integration.